2021
DOI: 10.1186/s12894-021-00819-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic diagnostic ureteroscopy using the VISERA ELITE video system for diagnosis of upper-urinary tract urothelial carcinoma: a prospective cohort pilot study

Abstract: Background The advantages of photodynamic diagnostic technology using 5-aminolevulinic acid (ALA-PDD) have been established. The aim of this prospective cohort study was to evaluate the usefulness of ALA-PDD to diagnose upper tract urothelial carcinoma (UT-UC) using the Olympus VISERA ELITE video system. Methods We carried out a prospective, interventional, non-randomized, non-contrast and open label cohort pilot study that involved patients who un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These findings were subsequently confirmed by two prospective trials [11,12 ▪ ]. Similarly, Wada et al [13 ▪ ] in their pilot study of PDD URS using VISERA ELITE video system reported that PDD could be superior to standard URS for CIS detection.…”
Section: Technologies To Improve the Diagnostic Accuracy Of Ureteroscopymentioning
confidence: 72%
“…These findings were subsequently confirmed by two prospective trials [11,12 ▪ ]. Similarly, Wada et al [13 ▪ ] in their pilot study of PDD URS using VISERA ELITE video system reported that PDD could be superior to standard URS for CIS detection.…”
Section: Technologies To Improve the Diagnostic Accuracy Of Ureteroscopymentioning
confidence: 72%
“…PDD utilises 5-aminovulinic acid to improve the visualisation of tumours and help distinguish abnormal tissue from benign tissue. Orally ingested 5-aminovulinic acid is metabolised to protoporphyrin IX which accumulates to a greater extent in tumour cells than in normal cells, and when excited with blue light emits red light via fluorescence [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The detection rate for UTUC with PDD has been shown to be significantly greater compared to traditional white light ureteroscopy, with several studies having found PDD to be more sensitive in diagnosing flat lesions and CIS than white light examination [ 72 , 74 ]. A meta-analysis of PDD use in the upper tracts reported a sensitivity to differentiate malignant lesions from benign of 96% with a specificity of 86% [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found that PDD improved the additional detection rate of UTUC compared with white-light ureteroscopy (RR 0.16, 95% CI 0.07-0.34 p-value=0.000) (28). Though PDD has demonstrated favorable outcomes, further validation remains to be seen, and clinically available systems may not demonstrate equivalent findings (37).…”
Section: Diagnostic Ureteroscopymentioning
confidence: 98%